Delivering Point-of-Care ultrasound teaching using a video conferencing technique - Tang, Evan; Daniel, Ryan; Wintraub, Lauren; Nelms, Matthew W; Heslop, Claire; Cho, Dennis Dane; Otremba, Mirek (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Implication StatementPoint-of-care ultrasound (POCUS) has usually been taught using a hands-on, in-person approach. We present a novel approach to delivering POCUS virtually using a dual image videoconferencing technique. We outline an easily implementable approach and summarize medical students’ experience and feedback. This form of delivery has potential to improve instructional delivery in resource restricted settings or during pandemic restrictions where a hands-on approach may not be possible.